'Phoenix' reflectarray unit cell with reduced size and inductive loading. Issue 12 (1st September 2016) - Makdissy, Tony; Gillard, Raphaël; Fourn, Erwan; Ferrando‐Rocher, Miguel; Girard, Etienne; Legay, Hervé; Le Coq, Laurent
Abstract : This study presents a new Phoenix unit cell with reduced size ( λ 0 /3 at centre frequency). Three different techniques are investigated to preserve a complete 360° phase range, with quasi‐linear and parallel phase responses over a reasonable frequency band, in spite of this small size. The phase cycle successively uses two different printed elements with complementary capacitive and inductive responses. The studied techniques aim at increasing the insufficient inductive effect. As a demonstration, a 1877‐element reflectarray is fabricated with the technique compatible with a single‐substrate fabrication process. Measured results show a 1 dB gain bandwidth of 11.3%.